Human papilloma virus: from understanding of immunopathogenesis to rational tactics of management - A L Tikhomirov; S I Sarsaniya; G A Filatova (IP Berlin A.V., 2018)
The human papilloma virus (HPV) is the most common sexually transmitted infection. 440 million people in the world suffer from HPV infection of the genital. During the life of HPV, 50 to 80% of the sexually active population is infected, most often in the first years of sexual activity (the maximum prevalence is between 18-30 years of age). The treatment of subclinical forms of HPV epithelial lesions in 115 patients aged 26 to 42 years with a normal colposcopic pattern and the presence of coilocytosis was performed.